Manufacture of pesticide from tobacco waste - Barangan, Anastacia Rosario; Donado, Rowena Liza.; Villafranca, Josielyn (Quezon City College of Engineering, 1989)
The plant is designed to manufacture nicotine sulfate from tobacco waste by extraction using water as a solvent and kerosene as eluting agent. In this method, 85% of the nicotine is recovered. The product is 40% nicotine sulfate, and the extracted waste meal is also sold as fertilizer. The plant has a total capacity of 2.1 tons per day of fertilizer. Twenty tons of tobacco waste is processed per day. Profit estimations reveal a 148% return of investment and a pay-out time of 7 1/2 months with a total investment of P 80,242,461.81.
Submitted in partial fulfillment of the requirements in ChE 62.
Keywords: Factories -- Design and construction; Botanical pesticides; Tobacco